Comparative Quantitative Study on Phytochemical Contents and Antioxidant Activities of Capsicum annuum L. and Capsicum frutescens L. - Tomi Lois Olatunji; Anthony Jide Afolayan (The Scientific World Journal)
The variabilities in the phytochemical contents and antioxidant activities of four varieties of two closely related cultivated Capsicum species, C. annuum and C. frutescens, were examined as an additional tool for establishing their phylogenetic relatedness and for breeding purposes. The methodology involved the use of ethanolic and aqueous extractions for the determination of the phytochemical and antioxidant properties. The phytochemical contents including total flavonoid, total phenol, and proanthocyanidins were evaluated spectrophotometrically while the antioxidant activities were determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS), nitric oxide (NO), and phosphomolybdenum assays. To point out the relationship among the varieties, a dendrogram based on the antioxidative phytochemical contents was constructed using the unweighted pair group method with arithmetic mean (UPMGA) cluster analysis. In all, aqueous extracts gave higher yield while ethanolic extracts showed higher phytochemical content across the varieties. Significant variations were observed among the varieties in relation to their phytochemical constituents and antioxidant activities. Dendrogram obtained from multivariate analysis distinguished the two Capsicum species. The first cluster contained only C. frutescens var. baccatum while the second cluster contained the three varieties of C. annuum species in subclusters, signifying the close genetic affinity among the three varieties. It also revealed that the four varieties are of a common progenitor. Information from this study gives additional evidence of chemotaxonomic significance and baseline data for effective selection of suitable parental genotypes in breeding for nutritional and pharmacological purposes.